A novel environmental vibration analysis system and its application in isolation of environmental vibration induced by high-speed train in Harbin frozen soil site. (May 2022) - Wang, Zhongyue; Tang, Aiping; Huang, Delong; Wu, Can; Huang, Ziyuan
Highlights: Overcomes a significant obstacle in train-induced environmental vibro-acoustic issue. Proposes a novel environmental vibration analysis system with a series of advantages. Example of its excellent application in cold HSR sites is given and validated. Blanks in current research on WIB vibration isolation in cold regions are well filled. A dynamic response prediction formula with reference value is given and validated. Abstract: Environmental vibration caused by high-speed trains and environmental noise pollution induced by such vibrations is one of the most challenging problems for sustainable urban development. One of the significant obstacles in analysis methods of vibration propagation path control is the inaccuracy caused by either over simplification of the interaction between train load and track above soil layers, or inappropriate expression of constitutive relationship and dynamic performance of soil below the track, especially in frozen soil, as difficulties and uncommonness exists in cross-application of multiple other disciplines into field of vibration and acoustics. A novel analysis system established in this paper, which is rare but very suitable for analysis of train induced environmental vibration and vibration isolation, builds a bridge for joint application of UM, ABAQUS, Python programming language and a series of derivation and calculation process, and manages to overcome the above obstacle to obtain a satisfactory solution. Field monitoring tests and accompanied numerical analysis based on parameters and properties determined by site investigation are carried out on soil vibration caused by CRH380B Harmony EMU train and its isolation at Harbin-Mudanjiang high-speed railway in China. Validations of the analysis system runs through the whole analysis process, including important processes and result data such as vertical wheel-rail force, velocity, vertical acceleration, characteristic frequency, and acceleration attenuation coefficient, etc. The results show that the established analysis system has high precision and wide application range, and vibration isolation effect with wave impeding barrier, who has better structural stability compared with other ones in cold regions under strong influence of seasonal and temperature physical effects, is excellent (vertical acceleration vibration level almost drop by more than 10 dB to below 72 dB, acceleration attenuation coefficient all below half and even a quarter in relatively close position). Blank in current research on wave impeding barrier vibration isolation of frozen soil sites in cold regions is well filled, and a dynamic response prediction formula is given and verified for the first time, which may have certain significance and reference value for other in-depth research.